Exergetic sustainability comparison of turquoise hydrogen conversion to low-carbon fuels - Banu, Aliya; Midilli, Adnan; Bicer, Yusuf (ELSEVIER SCI LTD, 2023)
Turquoise hydrogen is produced from methane cracking, a cleaner alternative to steam methane reforming. This study evaluates two proposed systems based on solar methane cracking for low-carbon fuel production. The systems employ different pathways to convert the turquoise hydrogen into a suitable form for transportation and utilize the carbon solid by-product. A direct carbon fuel cell is integrated to utilize the carbon and capture the CO2 emissions. The generated CO2 is utilized for fuel production using CO2 hydrogenation or co-electrolysis. An advanced exergetic analysis is conducted on these systems using Aspen plus simulations of the process. The exergetic efficiency, waste exergy ratio, exergy destruction ratio, exergy recoverability ratio, environmental effect factor and the exergetic sustainability index were determined for each system and the subsystems. Solar methane cracking was found to have an environmental effect factor of 0.08 and an exergetic sustainability index of 12.27.
Keywords: Hydrogenation; Low carbon fuels; Exergy; Sustainability index; Environmental effect; Solar energy; METHANE DECOMPOSITION; CO2 HYDROGENATION; HIGH-TEMPERATURE; DIMETHYL ETHER; INTEGRATION; CRACKING; ENERGY; CELLS; ELECTROLYSIS; INDICATORS; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology